Safety evaluation of the food enzyme 4‐α‐glucanotransferase from the genetically modified Bacillus amyloliquefaciens strain MAS - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme 4‐α‐glucanotransferase (1,4‐α‐d‐glucan:1,4‐α‐d‐glucan 4‐α‐d‐glycosyltransferase; EC2.4.1.25) is produced with the genetically modified Bacillus amyloliquefaciens strain MAS by Coöperatie Koninklijke Avebe U.A. The production strain contains multiple copies of known antimicrobial resistance genes. However, based on the absence of viable cells and DNA from the production organism in the food enzyme, this is not considered to be a risk. The food enzyme is intended to be used in the production of enzymatically treated starch. Dietary exposure to the food enzyme total organic solids (TOS) was estimated to be up to 0.012 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1000 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 83,333. A search for homology of the amino acid sequence of the 4‐α‐glucanotransferase to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure cannot be excluded, but that the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.